Physical activity advocacy in the UK: a multiple streams analysis of a hybrid policy issue. Issue 5 (3rd September 2017) - Piggin, Joe; Hart, Louise
Abstract: Physical activity is increasingly being defined as a major, complex, multi-sector issue. In order to understand more about how this expanded conception of physical activity is being factored into public policy, this article applies the multiple streams theory of policy change to examine the United Kingdom (UK) physical activity domain. Participant observation, policy analysis and media analysis are combined to examine the ways in which the political context, problem framing and policy solutions were brought together by a range of policy entrepreneurs. The study pays particular attention to how one lobby effort in the UK, the All Party Committee on Physical Activity (APCPA) attempted to elevate physical activity to a higher level of importance. The findings show how a hybrid form of organisation made up of traditional interest groups, corporations and government insiders, has successfully decreased ambiguity about physical activity and increased both official and public attention about the issue. The article suggests that while the multifarious benefits of physical activity and the diverse range of organisations involved have contributed to momentum towards policy change, these factors may also inhibit physical activity from remaining high on the policy agenda. Suggestions are offered for policy practices at a national level.